Lower wages for less hours? A simultaneous wage-hours model for Germany - Elke Wolf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
In this paper the impact of working hours on the gross hourly wage rate of West German women is analyzed. We use a simultaneous wage-hours model which takes into account the participation decision. First, our estimates show that the hourly wage rate is strongly aected by the working hours. In order to avoid any assumptions about the functional form, we estimate linear spline functions. Second, we detect dierent wage-hours profiles for specific groups of individuals. Despite these dierences, the wage reduction for jobs with less than 20 hours a week and for overtime hours turns out to be a robust result. However, the hourly wage rate of jobs with 20 to 38 hours does not dier significantly. Third, for West German women, the exogeneity assumption of working hours in the wage regression must be rejected if the wage-hours locus is assumed to be the same for all individuals. As a result of this the wage rate of full-time employees is overestimated in the standrad OLS estimation.
Keywords: J24; J22; J31; 330; Zeitlohn; Frauenarbeitslohn; Arbeitszeit; Teilzeitarbeit; Humankapital; Schätzung; Deutschland